Strategic Human Resources Management Practices and Employee Commitment: Literature Review - Erna Herlina; Martinus Tukiran; Muhammad Tito Andrianto; Hermansyah Hermansyah; Arief Teguh Nugroho (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Employee commitment is considered a key factor in achieving organizational goals. Employee commitment is one of the indicators of success in implementing strategic human resource management practices. In addition, organizational commitment is also stated as an antecedent of various indicators of organizational success. This paper aims to review the relationship between strategic human resource management practices and employee commitment. The findings of the literature review show that strategic human resource management practices have a direct positive effect on employee commitment. Employee commitment also has a role in mediating the relationship between strategic human resource management practices and human resource development andsustainable competitive advantage.